2013
DOI: 10.1152/physiolgenomics.00111.2013
|View full text |Cite
|
Sign up to set email alerts
|

Haploinsufficiency of osterix in chondrocytes impairs skeletal growth in mice

Abstract: (Osx) is essential for both intramembranous or endochondral bone formation. Osteoblast-specific ablation of Osx using Col1␣1-Cre resulted in osteopenia, because of impaired osteoblast differentiation in adult mice. Since Osx is also known to be expressed in chondrocytes, we evaluated the role of Osx expressed in chondrocytes by examining the skeletal phenotype of mice with conditional disruption of Osx in Col2␣1-expressing chondrocytes. Surprisingly, Cre-positive mice that were homozygous for Osx floxed allele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 31 publications
2
19
0
Order By: Relevance
“…Previous studies have shown that Osx is required for osteoblast differentiation and bone formation during embryonic development as well as in growing and adult bones . Although these studies focused on the role of Osx expressed in osteoblastic lineage cells in skeletal development, it has recently become known that Osx is also expressed in chondrocytes at certain stages during development and that mice with disruption of Osx in Col2‐expressing chondrocytes fail to thrive after birth owing to defects in skeletal maturation . Consistent with a role for TH‐induced Osx in the development of chondro/osteoblasts, Hammond and Schulte‐Merker have demonstrated evidence for the presence of Osx‐positive cells that coexpress chondrocyte and osteoblast differentiation markers during certain stages of zebrafish development.…”
Section: Discussionmentioning
confidence: 71%
“…Previous studies have shown that Osx is required for osteoblast differentiation and bone formation during embryonic development as well as in growing and adult bones . Although these studies focused on the role of Osx expressed in osteoblastic lineage cells in skeletal development, it has recently become known that Osx is also expressed in chondrocytes at certain stages during development and that mice with disruption of Osx in Col2‐expressing chondrocytes fail to thrive after birth owing to defects in skeletal maturation . Consistent with a role for TH‐induced Osx in the development of chondro/osteoblasts, Hammond and Schulte‐Merker have demonstrated evidence for the presence of Osx‐positive cells that coexpress chondrocyte and osteoblast differentiation markers during certain stages of zebrafish development.…”
Section: Discussionmentioning
confidence: 71%
“…For Western blot analysis, Osx antibody (ab22552; Abcam Inc.) and Phd2 antibody (#4835; Cell Signaling Technology, Inc., Danvers, MA, USA) were used at a 1:1000 dilution. Immunohistochemistry was carried out with paraffin sections of 5‐week femoral metaphysis as described . Osx antibody was used at a dilution of 1:500 and osteocalcin (OC) antibody (ab93876; Abcam Inc., Cambridge, MA, USA) at a dilution of 1:300.…”
Section: Methodsmentioning
confidence: 99%
“…Osx is a key regulator in osteoblast differentiation and maturation. Osx haploinsufficiency in mouse chondrocytes exhibited delayed growth of both trabecular and cortical bones [11-13]. Osx-null mice with the complete absence of intramembranous and endochondral bone formation died immediately after birth [14].…”
Section: Introductionmentioning
confidence: 99%